Before and After the Global Financial Crisis : Evaluating the Caribbean's Synchronization with Global Engines of Growth - Kouame, Auguste; Reyes, M. Ivanova (World Bank, Washington, DC, 2016)
In spite of the United States' recovery, most Caribbean nations are still struggling in the aftermath of the 2007–08 global financial crisis. This paper examines this slow growth recovery through the analysis of how the Caribbean's growth relates to that of key drivers of the global economy. The paper explores whether the region's links with some important global partners could be behind the sluggish post-crisis recovery. The paper analyzes the economic growth of Caribbean countries as a function of the growth in key global partners and of country-specific characteristics. The findings attribute an important role to the European Union and the United States in the outcomes for the region, especially in services-oriented economies. The findings show that when these nations grow, or when they are in an expansionary cycle, the Caribbean's growth responds positively but less than proportionally. Consequently, the slow recovery in the Caribbean region is attributed to the persistent sluggishness in the European Union and the fact that the U.S. recovery is still nascent and not quite robust.